Geogenic and anthropogenic contamination in river water and groundwater of the lower Cauvery Basin, India - Keerthan, Lingaiah; RamyaPriya, Ramesh; Elango, Lakshmanan (Frontiers in Environmental Science, 2023)
Degradation of water quality is a major challenge in both developed and developing countries since it poses a great risk to ecological health. The Cauvery river is one of the most important rivers of southern India, where the effect of seasonal variation on the quality of river water and its adjoining groundwater on the lower part of the basin has not yet been studied. Hence, the present study was carried out to evaluate the river water and adjacent groundwater for drinking and irrigational purposes, and also to identify the sources affecting the water quality. About 118 river water and 131 groundwater samples were collected over 4 months from May 2018 to August 2019. The water samples were analyzed for electrical conductivity (EC), pH, major and minor ions, and trace elements. The major, minor, and trace elements were then compared with the Bureau of Indian Standards and World Health Organization for drinking water quality assessment. The drinking water quality was assessed, indicating that both river water and groundwater were unsuitable in the coastal regions, especially during dry seasons. Irrigation water quality was also assessed, which indicates that most of the river water and groundwater samples were unsuitable near the coastal region. The quality of river water and groundwater in the lower Cauvery Basin was found to be better during wet periods compared to the dry season. It was observed that the rock–water interactions was the major factor controlling the water quality for groundwater and surface water, followed by anthropogenic activities such as disposal of domestic sewage and effluents into the river, as runoff from irrigated lands. The study emphasizes the development of a finer observational network for water quality, along with stringent monitoring of the disposal of contaminants in the rivers and groundwater.